Influence of Social Media and Internet on Treatment Decisions in Adult Female Acne Patients: A Cross-Sectional Survey Study - Ertekin, Sumeyre Seda; Salici, Nazmiye Selin; Manav Baş, Vildan; Göre Karaali, Müge; Ergün, Ecem Zeliha; Avcı, Elif Bal; Sarıkaya Tellal, Ebru; Yüksel, Esma Inan; Rasulova, Günel; Erdil, Duygu (Dermatology Practical & Conceptual, 2024)
Introduction: Adult female acne is a chronic condition that significantly impacts quality of life. The content on social media can influence patients’ perception of their disease and serve as a channel through which they may seek or obtain treatment options. Objectives: This study aims to evaluate the impact of social media usage habits on treatment decisions among adult female acne patients. Methods: A cross-sectional, multicenter survey study involved 358 females aged 25 or above, diagnosed with acne. Sociodemographic data were collected, and social media behavior, treatment choices, outcomes, and motivation were explored. Results: Among 358 participants, 95.3% used at least 1 social media platform; 72.1% sought acne information online. Top platforms used to seek acne information were Google (75.6%), Instagram (72.3%), YouTube (60%), and TikTok (29.4%). For advice, 67.4% consulted doctor accounts, 53.5% non-medical influencers, 53.5% patient accounts, and 36.1% product promotion accounts. Commonly followed advice included skincare products (88%), dietary changes (42.3%), home remedies (38.8%), exercise (30.3%), topical medications (25.2%), and dietary supplements (17.4%). Notably, 20.9% were willing to alter prescribed treatment by their physician for acne based on social media advice. Patient motivations included quick information access (84.1%) and difficulty in securing dermatologist appointments (54.3%). Conclusion: The study reveals widespread social media use among adult female acne patients, highlighting concerns about potentially misleading information. Dermatologists can enhance the impact of social media by providing reliable sources for patients.